2016
DOI: 10.1590/0103-9016-2015-0159
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of ammonia from anaerobically digested manure using gas-permeable membranes

Abstract: Nitrogen (N) can be recovered from different types of wastewaters. Among these wastewaters, anaerobically digested swine manure (digestate) has the highest N content in ammonia form (NH 3 ). It is desirable to reduce N in digestate effluents to safely incorporate them in arable soil in N vulnerable zones (NVZ) and to mitigate NH 3 emissions during N land application.Additional benefit is to minimize inhibition of the anaerobic process by removing NH 3 during the anaerobic digestion process. This work aimed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 13 publications
1
19
0
Order By: Relevance
“…Tunes et al (2012) have reported that the presence of organic acids which originating from the anaerobic decomposition of organic material can significantly reduce the germination of wheat cultivars, radicle length and dry weight. It is well known that concentration of ammonia in digested manure is higher compared to raw manure (García-González et al 2016), which was found to reduces wheat seed germination and suppresses root hair formation (Bremner and Krogmeier 1989;Wan et al 2016). The adverse effect of combining manure with urea on seeds germination and radicle length have been reported in another study where they referred this adverse effect to the presence of ammonia, which formed through hydrolysis of urea by soil urease (Bremner and Krogmeier 1989).…”
Section: Seedlings Dry Weightmentioning
confidence: 94%
See 1 more Smart Citation
“…Tunes et al (2012) have reported that the presence of organic acids which originating from the anaerobic decomposition of organic material can significantly reduce the germination of wheat cultivars, radicle length and dry weight. It is well known that concentration of ammonia in digested manure is higher compared to raw manure (García-González et al 2016), which was found to reduces wheat seed germination and suppresses root hair formation (Bremner and Krogmeier 1989;Wan et al 2016). The adverse effect of combining manure with urea on seeds germination and radicle length have been reported in another study where they referred this adverse effect to the presence of ammonia, which formed through hydrolysis of urea by soil urease (Bremner and Krogmeier 1989).…”
Section: Seedlings Dry Weightmentioning
confidence: 94%
“…This negative effect has been attributed to the contaminants that generated during decomposition of organic waste such as ethylene oxide (Wong et al 1983) and organic acid (Bacilio et al 2003;Makádi et al 2012). Moreover, the concentration of ammonia in digestate is high (García-González et al 2016) and this can reduce and delay wheat seeds germination (Bremner and Krogmeier 1989;Wan et al 2016). In fact, it is unclear if this adverse effect will last for a short or long period and thus can be avoided by adjusting the cultivation strategy, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The gas-permeable membrane technology has been successfully applied to recover up to 99% of TAN from swine manure and anaerobically digested swine manure [5,14,[21][22][23]. Previous research mainly focused on the influence of operational conditions such as animal waste strength and pH on TAN recovery using gas-permeable membranes always operated at batch mode.…”
Section: Introductionmentioning
confidence: 99%
“…Some technologies have been used to reduce the excess N content in livestock wastewater, promoting its recovery in the mineral form (NH + 4 ) and allowing its reuse as agricultural fertilizer in areas far from the livestock concentration with greater needs for the N nutrient. Dube et al (2016) and Garcia-Gonzalez et al (2016) used a new process utilizing gas-permeable membranes (GPM) in low pressure systems to capture the N present in the digestate from the anaerobic mono-digestion of SM and store it in a concentrated form in an acid solution of 0.5 M H 2 SO 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Successful N recovery using GPM has already been performed on different organic wastes such as poultry litter (Rothrock et al, 2010(Rothrock et al, , 2013, swine manure (Garcia-Gonzalez and García-González et al, 2015) and digestate from mono-digestion of swine manure (Dube et al, 2016;Garcia-Gonzalez et al, 2016;Vanotti et al, 2017) with NH + 4 recovery above 90% of the total content of this form of the nutrient in the residues. However, recovery of N in the digestate from systems operating in ACoD has not yet been performed.…”
Section: Introductionmentioning
confidence: 99%